Eustachian Tube Balloon Dilation: Emerging Practice Patterns for a Novel Procedure. (November 2018) - Micucci, Steven; Keschner, David B; Liang, Jonathan
Objectives: To review the role of eustachian tube balloon dilation (ETBD) in the setting of chronic Eustachian tube dysfunction (ETD) and ascertain how ETBD is currently being used in practice today. Methods: An online survey included 20 questions designed by 3 investigators to examine how otolaryngologists utilize ETBD in the management of ETD. The survey was distributed to the members of the American Rhinologic Society (ARS), American Otological Society (AOS), and American Neurotology Society (ANS) in their respective annual electronic mailings in April and May of 2017. Results: A total of 1105 and 633 surveys were sent to ARS and AOS/ANS members, respectively. Of those, 157 surveys were returned (126 from ARS and 31 from AOS/ANS). Of those returning the survey, 72 (50%) had not performed ETBD and were excluded from subsequent analysis. Forty-four (66%) respondents consider ETBD after failure of medical management; conversely, 18 (27%) and 26 (39%) consider ETBD after failure of 1 or more trial of myringotomy tube placement. Routine testing for ETBD includes audiogram with tympanometry 64 (96%) and preoperative computer tomography (CT) 38 (57%). Fifty-three (80%) practitioners only perform ETBD in adults 18 years and older. Thirty-four (53%) respondents describe ETBD as "great" or "good, " while 27 (42%) were unsure, and only 3 (5%) did not like ETBD. Conclusions: Eustachian tube balloon dilation is a novel technique for the treatment of chronic ETD, and its role continues to evolve and develop. Current practice patterns demonstrate wide variability in the assessment of ETD, heterogeneity in the timing of ETBD, and controversy in preoperative CT screening.